2021
DOI: 10.1021/acsaem.1c02125
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundary Defects Passivated with tert-Butyl Methacrylate for High-Efficiency Perovskite Solar Cells

Abstract: A high-quality perovskite film is critical to realize high-efficiency and hysteresis-less perovskite solar cells (PSCs). However, a solution-processed perovskite layer presents many ionic vacancies on grain boundaries, which serve as nonradiative recombination centers that cause a loss of photocurrent. Herein, a trace amount of Lewis base tert-butyl acrylate (TBA) with both effective CO and CC functional groups is introduced to synergistically control the crystallization process and saturate surface dangling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…4(b), the slope can be proportional to the trap-assisted recombination of solar cells. 39,40 The slope of the EMIM DEP-based device is deduced to be 1.27 k B T/q, lower than 1.34 k B T/q for the control device, where k B is the Boltzmann constant, and T is the absolute temperature. This means that defect-induced charge recombination is signicantly reduced in the EMIM DEP-based device.…”
Section: Resultsmentioning
confidence: 99%
“…4(b), the slope can be proportional to the trap-assisted recombination of solar cells. 39,40 The slope of the EMIM DEP-based device is deduced to be 1.27 k B T/q, lower than 1.34 k B T/q for the control device, where k B is the Boltzmann constant, and T is the absolute temperature. This means that defect-induced charge recombination is signicantly reduced in the EMIM DEP-based device.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the entire conjugated structure can serve as a bond to provide a channel for transporting photogenerated carriers on the film surface, preventing excessive charge accumulation at the grain boundary, improving the carrier transport performance, which will be further verified in the subsequent photoelectric performance analysis. [ 18,42–44 ] It is obvious from the above analysis that the PSCs performance modified by K‐NAA doping can be improved in all aspects. These improvements are mainly attributable to the higher film quality, better carrier transport performance, and less nonradiative recombination brought about by passivation.…”
Section: Resultsmentioning
confidence: 99%
“…[ 17 ] Moreover, by plasma crosslinking polymerization with Pb 2+ , the CO bond in the ester group can strengthen the anchoring effect on the crystal surface. [ 18 ] As a result, the ester group, which can exert numerous passivation effects, is regarded as a significant and efficient group in improving the performance of PSCs. Sun et al demonstrated that according to Goldschmidt tolerance factors, [ 19 ] metal ions such as K + , [ 20 ] Rb + , [ 21 ] Cu + , [ 22 ] Ni 2+ , [ 23 ] Zn 2+ , [ 24 ] Al 3+ , [ 25 ] and Sb 3+ [ 26 ] are too tiny that incorporated into perovskite crystals.…”
Section: Introductionmentioning
confidence: 99%
“…PBN has three different kinds of functional groups, as shown in Figure 1b: the zwitterionic nitrone (N + -O − ) group can passivate both types of charged defect sites via electrostatic interactions (Figure S1, Supporting Information); the tert-butyl (-C(CH 3 ) 3 ) group has hydrogen bonding sites that interact with the RPP materials and suppress ion migration; and the aromatic ring acts as a Lewis base to form acid-base adducts with specific Lewis acid-type defects in the RPP materials. [50][51][52] Therefore, the PBN passivation molecule is expected to passivate numerous defects in the RPP materials effectively.…”
Section: Resultsmentioning
confidence: 99%